2019
DOI: 10.17744/mehc.41.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Transcendent Characteristics as Predictors of Counselor Professional Quality of Life

Abstract: Although counselors do meaningful work, they can also experience compassion fatigue as a result of counseling clients. Relatively few studies have focused on how counselors' positive characteristics might contribute to their professional quality of life. This study combined the transcendent constructs of gratitude, hope, and daily spiritual experiences as predictors of counselor burnout and compassion satisfaction. Counselors (N = 98) completed a survey assessing professional quality of life and constructs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 48 publications
1
17
1
Order By: Relevance
“…We studied the relationships among prelicensed counselors’ individual and organizational demographic variables, professional quality of life (i.e., compassion satisfaction, burnout, and secondary traumatic stress), and affective distress (i.e., depression, anxiety, and stress) using structural equation modeling. When compared with Browning et al (2019), participants in our study scored slightly lower in compassion satisfaction, higher in burnout, and lower in secondary traumatic stress. We were unable to compare participants from the present study with those from the Lawson and Myers (2011) study because of the different ProQOL versions administered between studies.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…We studied the relationships among prelicensed counselors’ individual and organizational demographic variables, professional quality of life (i.e., compassion satisfaction, burnout, and secondary traumatic stress), and affective distress (i.e., depression, anxiety, and stress) using structural equation modeling. When compared with Browning et al (2019), participants in our study scored slightly lower in compassion satisfaction, higher in burnout, and lower in secondary traumatic stress. We were unable to compare participants from the present study with those from the Lawson and Myers (2011) study because of the different ProQOL versions administered between studies.…”
Section: Discussioncontrasting
confidence: 75%
“…The numerous challenges experienced by prelicensed counselors may help contextualize the findings by scholars (e.g., Browning et al, 2019; Thompson et al, 2014) who reported an inverse correlational relationship between years of experience and counselor burnout. That is, as counselors’ years of experience decreased, their self‐reported symptoms of burnout increased.…”
Section: Prelicensed Counselorsmentioning
confidence: 84%
See 3 more Smart Citations